Dreading delayed punishment: Reconceptualizing sanction "celerity". Issue 3 (27th May 2022) - Jaynes, Chae M.; Wilson, Theodore
ABSTRACT: The celerity tenet has traditionally been interpreted to suggest that a swift punishment is more effective than one that is delayed because it is more aversive, which should prompt individuals to prefer delayed punishments. This article suggests an alternative – that individuals prefer immediate sanctioning because delayed sanctions may invoke costly negative emotions. Sanction temporal preferences are investigated among young adults who answered questions pertaining to scenarios while sanction type, severity and timing were varied. Contrasting classical expectations, findings suggest that respondents expressed strong and consistent preferences for immediate sanctioning; a preference which was more tenuous among financial sanctions. Our findings underscore the need to consider preferences surrounding sanction timing more carefully.